ANALYSIS OF MANAGEMENT ACCOUNTABILITY OF KPN BINA ACCORDING TO THE CONCEPT OF SHIRKAH 'INÂN IN ISLAMIC ECONOMIC LAW - Qurratulaini, Intan; Chamsa Amara (Al-Mudharabah: Jurnal Ekonomi dan Keuangan Syariah, 2023)
Every cooperative operation must be closely monitored by the supervisory board, including KPN Bina Sejahtera which periodically based on the provisions in the AD/ART must audit operations and financial bookkeeping with all its business activities, but KPN Bina Sejahtera which is located in Kec. In the Aceh Besar Seulimeum, there are still many problems that are not in synergy with cooperative regulations, including their internal rules. The formulation of the problem is what the provisions for auditing KPN Bina Sejahtera's financial reporting are and the responsibility of the management to implement the results of the pre-RAT audit and the syirkah 'inân review of the financial reporting audit system at KPN Bina Sejahtera. The research approach uses normative sociological research with descriptive analytical research. Data collection techniques use interviews and documentation data. The research results showed that the auditing carried out by KPN Bina Sejahtera supervisors was carried out only as a formality in fulfilling the needs of the RAT. The KPN Bina Sejahtera management did not make the latest provisions regarding the management of cooperative businesses in accordance with the latest cooperative regulations, so the AD/ART still does not meet the standard provisions for cooperatives in Aceh which must comply with the principles based on the LKS Qanun as its formal juridical basis. Weaknesses in KPN Bina Sejahtera's supervisory audit were also found in principal savings and mandatory savings which were not in accordance with cooperative capital provisions. Based on the data obtained, the determination of profit sharing at KPN Bina Sejahtera is relevant to the concept of syirkah 'inan, however, the audit system carried out by the supervisory board for the accountability needs of the RAT KPN Bina Sejahtera towards the management of the cooperative for the needs for profit sharing is not accountable and transparent, so it can be stated that the management of KPN Bina Sejahtera is not relevant to the provisions of business management using the syirkah 'inan pattern.